Dysfunctional microbiota with reduced capacity to produce butyrate as a basis for allergic diseases - Macia, Laurence; Mackay, Charles R. (Journal of allergy and clinical immunology, 2019)
In the 1-year-old microbiome they found that the total number of CAZyme genes in families that degrade plant cell-wall, animal, and fungal carbohydrates were depleted in children who became atopic relative to control subjects. [...]the microbiome of children who became atopic had less capacity to degrade the resistant starch in their diet also at 1 year. [...]it is striking that children with atopy have, from early stages of life, a dysfunctional microbiome with a poor ability to efficiently degrade complex carbohydrates derived either from milk or food. Butyrate and acetate were behind the beneficial effects of high fiber in a food allergy model in mice through their binding of GPR43 and GPR109a.6 Propionate and GPR41 are protective in mice with asthma-like allergic airway inflammation.10 SCFAs might also promote Treg cells through epigenetic changes caused by inhibition of histone deacetylases, with acetate protecting from asthma-like inflammatory diseases in mice through increases in Treg cell numbers caused by histone deacetylase 9.5 SCFAs promote Treg cells either directly by promoting peripheral Treg cell development from naive T cells or indirectly through effects on CD103+ dendritic cells (the master regulators of mucosal tolerance).6 A summary of all the cellular and molecular mechanisms that might be leading to allergy/asthma is presented in Fig 1.